Saving the style forming features of Art Nouveau in the historical building - Sidurova E., E.; Chertov, D. (Theory and practice of design, 2016)
In the article the style forming factors of Art Nouveau (known as Modern in Ukraine and Russia) are considered on the example of Kyiv building development in the end of the 19th - beginning of the 20th century. The most typical elements of Kyiv building facades in the Art Nouveau style were revealed and the use of these elements was suggested for the reconstruction and new architectural inclusions in the historical structure of the city.